Light hydrocarbon geochemical characteristics and their application in Upper Paleozoic, Shenmu gas field, Ordos Basin. Issue 1 (January 2017) - Han, Wenxue; Tao, Shizhen; Hu, Guoyi; Ma, Weijiao; Liu, Dan; Feng, Ziqi; Peng, Weilong
Light hydrocarbon has abundant geochemical information, but there are few studies on it in Shenmu gas field. Taking Upper Paleozoic in Shenmu gas field as an example, authors use gas chromatography technology to study light hydrocarbon systematically. The results show that (1) The Shenmu gas field is mainly coal-derived gas, which is mixed by partial oil-derived gas due to the experiment data. (2) Based on K 1, K 2 parameter and Halpern star chart, the Upper Paleozoic gas in Shenmu gas field belongs to the same petroleum system and the depositional environment of natural gas source rocks should be homologous. (3) The source rocks are mainly from terrestrial higher plant origins and belong to swamp facies humic due to methyl cyclohexane index and Mango parameter intersection chart, which excluded the possibility of the Upper Paleozoic limestone as source rocks. (4) The isoheptane ranges from 1.45 to 2.69 with an average of 2.32, and n-heptane ranges from 9.48 to 17.68% with an average of 11.71%, which is below 20%. The maturity of Upper Paleozoic gas in Shenmu gas field is low-normal stage, which is consistent with R o data. (5) The Upper Paleozoic natural gas in the Shenmu gas field did not experience prolonged migration or secondary changes, thus can be analyzed by light hydrocarbon index precisely.